The main trends in the modern techniques of playing the wind instrument - Bakhtiyar Abdrashev, Victor Glebov, Olesya Nesterova, Vitaliy Shapilov, Galiya Begembetova, Gulnar Abdirakhman, (Opción, 2020)
The purpose of the study is to present the typology of contemporary methods of playing the flute, classifying them based on the properties of musical expressiveness. The empirical and theoretical approaches to the study were used as the research method. The results of a comprehensive study of experimental pieces for solo flute by foreign authors of the second half of the 20th century indicate new performing techniques become an integral part of the new music and modern composition techniques. In conclusion, the received results are relevant for writing compositions for wind instruments with the use of contemporary playing techniques.